Clinical Effect of Systemic Steroids in Patients with Cirrhosis and Septic Shock. Issue 6 (December 2021) - Piccolo Serafim, Laura; Simonetto, Douglas A.; Anderson, Alexandra L.; Choi, Dae Hee; Weister, Timothy J.; Hanson, Andrew C.; Kamath, Patrick S.; Gajic, Ognjen; Gallo de Moraes, Alice
ABSTRACT: Purpose: Evidence regarding the utility of systemic steroids in treating patients with cirrhosis and septic shock remains equivocal. This study aimed to evaluate and elucidate the association of steroid use with outcomes and adverse effects in a cohort of patients with cirrhosis and septic shock. Patients and methods: Retrospective cohort study of patients with cirrhosis and septic shock admitted to a tertiary hospital intensive care unit (ICU) from January 2007 to May 2017, using a validated ICU Datamart. Patients who received vasopressors within 6 h of ICU admission were included in the multivariate analysis. The effect of steroids on outcomes was evaluated using multivariable regression, adjusting for confounding variables. Results: Out of 179 admissions of patients with cirrhosis and septic shock, 56 received steroids during the ICU admission. Patients who received steroids received a higher total dose of vasopressors (91.2 mg vs. 39.1 mg, P = 0.04) and had a lower initial lactate level (1.8 mmol/L vs. 2.6 mmol/L, P = 0.007). The multivariate analysis included 117 patients and showed no significant differences in mortality, length of ICU admission, or length of hospital stay. Bleeding events, delirium, and renal-replacement therapy requirements were also not associated with the use of steroids. Conclusion: The use of systemic steroids was more prevalent in cirrhotic patients with higher vasopressor requirements. It was not associated with decreased mortality or increased ICU- and hospital-free days, or to adverse effects.